2022
DOI: 10.1371/journal.pone.0276801
|View full text |Cite
|
Sign up to set email alerts
|

The role of religious leaders on the use of HIV/AIDS prevention strategies among young people (15–24) in Lira district, Uganda

Abstract: Background Young people (15–24 years) bear the highest burden of new infections and are particularly vulnerable because of their highly risky behavior such as early sexual activity. There is paucity of information on the role of religious leaders in the multi-sectoral fight against HIV/AIDS. We examined the role of religious leaders in the use of HIV prevention strategies among young people. Methods A cross sectional study was conducted between March and April 2021 among 422 randomly selected young people in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, our ndings also revealed several barriers to the active participation of religious leaders in implementing HIV preventive initiatives among young people. These include con icting religious beliefs, inadequate knowledge about HIV prevention, and insu cient training on HIV prevention methods (7). Religious beliefs signi cantly in uence the decisions of religious leaders when recommending certain HIV prevention strategies, with some refraining from promoting condom use due to religious convictions (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our ndings also revealed several barriers to the active participation of religious leaders in implementing HIV preventive initiatives among young people. These include con icting religious beliefs, inadequate knowledge about HIV prevention, and insu cient training on HIV prevention methods (7). Religious beliefs signi cantly in uence the decisions of religious leaders when recommending certain HIV prevention strategies, with some refraining from promoting condom use due to religious convictions (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…While previous research indicates that religious leaders possess relatively good knowledge of HIV prevention, there is evidence of persistent misconceptions and negative attitudes toward certain prevention methods among some religious leaders (13,14). Moreover, studies have revealed a tendency among religious leaders to emphasize abstinence and faithfulness while providing limited support for condom use, despite the effectiveness of multi-strategy approaches to HIV prevention (7,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Furthermore, another study identified religious leaders as key stakeholders in the HIV/AIDS fight, despite their role being limited by a lack of training, inadequate equipment, and facilitation to carry out HIV prevention programs. 22 This could be due to the similarity of the population and the context. The role of the religious leaders and key individuals in the group who may have influence can negatively impact on adherence to ART.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the drawbacks of antiretroviral drugs, preventing HIV/AIDS spread is highly advocated. Recently, religious organizations have been reported to be of utmost importance in the dissemination of HIV/AIDS prevention protocols [20]. The role of religious organizations in the campaign against the HIV/AIDS scourge in SSA cannot be undermined due to their dignified societal status.…”
Section: Introductionmentioning
confidence: 99%